Vaccination coverage, barriers and vaccine hesitancy in children up to 24 months old: a population survey in a state capital in the Western Amazon - Thaiane Rodrigues de Oliveira Macedo; Maria Fernanda de Sousa Oliveira Borges; Ilce Ferreira da Silva; Ana Paula França; José Cássio de Moraes; Adriana Ilha da Silva; Alberto Novaes Ramos Jr; Ana Paula França; Andrea de Nazaré Marvão Oliveira; Antonio Fernando Boing; Carla Magda Allan Santos Domingues; Consuelo Silva de Oliveira; et al. (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To estimate vaccination coverage, identify barriers and hesitancy to vaccinating children up to 24 months, born between 2017-2018, living in the urban area of Rio Branco, Acre, Brazil. Methods Population survey carried out from 2020 to 2021, which assessed sociodemographic characteristics and vaccination status among children. Results Among 451 included children, vaccination coverage was below 80%. Meningococcal C vaccine had the lowest coverage for administered doses (76.3%; 95%CI 70.5;81.3) and doses on time (27.4%; 95%CI 23.1;32.1). The statements "vaccines cause serious adverse reactions" (26.4%; 95%CI 18.1;36.8) and "you don't need vaccination for diseases that no longer exist" (22%; 95%CI 15.7;29.8) were the most frequent regarding vaccination hesitancy. Lack of vaccines was the main barrier to care (86.6%; 95%CI 71.8;94.3). Conclusion Vaccination coverage in children born in 2017-2018 was below the target recommended for the full schedule of administered doses, both valid and timely administered.